Paracrine Factors of Human Fetal MSCs Inhibit Liver Cancer Growth Through Reduced Activation of IGF-1R/PI3K/Akt Signaling - Yulyana, Yulyana; Ho, Ivy A W; Sia, Kian Chuan; Newman, Jennifer P; Toh, Xin Yi; Endaya, Berwini B; Chan, Jerry K Y; Gnecchi, Massimiliano; Huynh, Hung; Chung, Alexander Y F; Lim, Kiat Hon; Leong, Hui Sun; et al. (Molecular therapy, 2015)
Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death in the world. The multikinase inhibitor sorafenib only demonstrated marginal improvement in overall survival for advanced disease prompted the search for alternative treatment options. Human mesenchymal stem cells (MSCs) have the ability to home to tumor cells. However, its functional roles on the tumor microenvironment remain controversial. Herein, we showed that conditioned media derived from human fetal MSC (CM-hfMSCs) expressed high level of the insulin growth factor binding proteins IGFBPs and can sequester free insulin-like growth factors (IGFs) to inhibit HCC cell proliferation. The inhibitory effect of IGFBPs on IGF signaling was further evident from the reduction of activated IGF-1R and PI3K/Akt, leading eventually to the induction of cell cycle arrest. We also demonstrated that CM-hfMSCs could enhance the therapeutic efficacy of sorafenib and sunitinib. To the best of our knowledge, this is the first report to show that CM-hfMSCs has a tumor-specific, antiproliferative effect that is not observed with normal human hepatocyte cells and patient-derived matched normal tissues. Our results thus suggest that CM-hfMSCs can provide a useful tool to design alternative/adjuvant treatment strategies for HCC, especially in related function to potentiate the effects of chemotherapeutic drugs.